2023
DOI: 10.3390/ijms24065778
|View full text |Cite
|
Sign up to set email alerts
|

Update on the Role and Regulatory Mechanism of Extracellular Matrix in the Pathogenesis of Uterine Fibroids

Abstract: Uterine fibroids (UFs), also known as leiomyomas, are benign tumors of the myometrium affecting over 70% of women worldwide, particularly women of color. Although benign, UFs are associated with significant morbidity; they are the primary indication for hysterectomy and a major source of gynecologic and reproductive dysfunction, ranging from menorrhagia and pelvic pain to infertility, recurrent miscarriage, and preterm labor. So far, the molecular mechanisms underlying the pathogenesis of UFs are still quite l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 115 publications
0
2
0
Order By: Relevance
“…The measurement of BRD9 expression was conducted in relatively small samples. UF heterogeneity occurs at many levels, including etiology, clinical symptoms, and pathogenesis, significantly impacting research design and therapeutic decisions [45]. In this study, we observed the variation of BRD9 expression in UFs.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…The measurement of BRD9 expression was conducted in relatively small samples. UF heterogeneity occurs at many levels, including etiology, clinical symptoms, and pathogenesis, significantly impacting research design and therapeutic decisions [45]. In this study, we observed the variation of BRD9 expression in UFs.…”
Section: Discussionmentioning
confidence: 67%
“…The results were consistent with the RNA-seq data (Figure S3A). Several studies have demonstrated that abnormal ECM accumulation and remodeling are critical for UFs [42][43][44][45]. Excessive ECM deposition and production can contribute to mechanotransduction, therefore regulating downstream signaling leading to the pathogenesis of UFs [46][47][48].…”
Section: Enrichment Pathway Analysismentioning
confidence: 99%
“…The next group of genes (KRT17, COL24A1, MMP17, MYOG, MYO5B, and GRIP1) with minimal to no alteration in matched myometrium in the White patients but with significantly higher expression in fibroids from Black and Hispanic patients were related to the cell cytoskeleton and ECM. One of the hallmark characteristics of fibroid tumors is the excess ECM production, which contributes to its stiffness [85][86][87]. The ECM is a reservoir of growth factors and cytokines, and changes in ECM stiffness result in signals that are converted into chemical changes [85].…”
Section: Discussionmentioning
confidence: 99%
“…Several mechanisms are proposed to explain the development and growth of UFs. Sex hormones, molecular changes in the extracellular matrix, growth factors, epigenetic and epitranscriptomic regulation and DNA damage repair pathways seem to play the most crucial role [ 3 , 4 ]. The problem of UFs is faced by up to 70% of women at menopausal age.…”
Section: Introductionmentioning
confidence: 99%